Імперативи розвитку міської муніципальної медицини - Новіков, В.М. (Інститут демографії та соціальних досліджень НАН України, 2009)
На основі диференційованої статистичної оцінки потенціалу муніципальної медицини обґрунтовується висновок щодо її кількісної й якісної невідповідності рівню
захворюваності міських жителів. Пропонуються сучасні інституційні, фінансово- економічні механізми й новітні медико-організаційні технології модернізації медичного обслуговування. На основе дифференцированной статистической оценки потенциала муниципального здравоохранения обосновывается вывод о его количественном и качественном несоответствии уровню заболеваемости городских жителей. Предлагаются современные институциональные, финансово-экономические механизмы и новые медико- организационные технологии модернизации медицинского обслуживания. In the article the influence of municipal health protection on the indexes of population morbidity is estimated on basis of territorial features within the limits of 35-80% from all complexes of factors which form a public health. There was analytically proved that to ensure full accessibility of urban residents to health services, municipal health resources should be increased three-fold. Improvement of municipal health-care system involves several directions, mechanisms of implementation which are summarized in the article. Institutional and organizational - allows for the creation of health districts to overcome the disparity territorial health care. Medical technology - at the expense of innovative treatments to improve the effectiveness of the resource potential of community medicine. Program-regional area will expand the use of multi-funding mechanism. Cross-sectoral - to form an interagency health and social services structure. Budget-governing - on the basis of improving inter-budgetary relations at the municipal level to the planning of regional policy and strategy development of health facilities. The development of integrative spatial directions should help communities to accumulate funds earmarked for health care. In general, article focuses on the formation of the systematic approach at the organization, financing and motivation of medical practice in the municipal sector.